2016
DOI: 10.1111/epi.13648
|View full text |Cite
|
Sign up to set email alerts
|

TRPC3 channels play a critical role in the theta component of pilocarpine‐induced status epilepticus in mice

Abstract: Summary Objective Canonical transient receptor potential (TRPC) channels constitute a family of cation channels that exhibit a regional and cell-specific expression pattern throughout the brain. It has been reported previously that TRPC3 channels are effectors of the BDNF/trkB signaling pathway. Given the long postulated role of BDNF in epileptogenesis, TRPC3 channels may be a critical component in the underlying pathophysiology of seizure and epilepsy. In this study, we investigated the precise role of TRPC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…2A,B) or pentylenetetrazol administration (Fig. 2C,D) failed as the neural activity after single administration of these chemical convulsants was far below the root mean square power of SE observed in unanesthetized mice 15 . However, we found that sequential administration of pilocarpine and pentylenetetrazol reliably induced seizures in anesthetized mice that were similar electrographically and behaviorally to the pilocarpine-induced seizures in unanesthetized mice (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…2A,B) or pentylenetetrazol administration (Fig. 2C,D) failed as the neural activity after single administration of these chemical convulsants was far below the root mean square power of SE observed in unanesthetized mice 15 . However, we found that sequential administration of pilocarpine and pentylenetetrazol reliably induced seizures in anesthetized mice that were similar electrographically and behaviorally to the pilocarpine-induced seizures in unanesthetized mice (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…pilocarpine-induced seizures and eeG recording. EEG head-mount surgery of age-matched (2.8 to 3-month-old) TRPC3smcKO and littermate control male mice was conducted as described previously 15 . Mice were administered a single dose of methylscopolamine nitrate (10 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Similar to our findings, pilocarpine-induced SE in mice increases theta activity in the preictal and SE phases. 30 In addition, case studies of patients diagnosed with idiopathic generalized epilepsy reveal increases in theta and delta power during interictal states. 31 Moving forward, it will be interesting to test in the ES1−/− mouse model of CWNA toxicity the hypothesis that drug treatments that reduce the observed increase in power of EEG activity in the 0.1-8 Hz frequency range would ameliorate chronic epileptic activity that follows prolonged benzodiazepine-resistant SE.…”
Section: Discussionmentioning
confidence: 99%
“…TRPC3 channels are found to be responsible for pilocarpine-induced status epilepticus (SE) in mice. The reduction on SE in TRPC3 KO mice is caused by a selective attenuation of pilocarpine-induced theta wave activity [103]. TRPC7 can be detected in CA3 pyramidal neurons largely.…”
Section: Canonical Transient Receptor Potential (Trpc)mentioning
confidence: 92%